Ṛgvedske himne Varuṇi in vprašanje moralnosti v stari vedski religioznosti Rigvedic Hymns to Varuṇa and the Question of Morality in Old Vedic Religion - Škof, Lenart (Studia mythologica Slavica, 2015)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The article discusses Varuṇa hymns of the Rigveda and specifically the presence of moral consciousness within the vedic religion together with its impact on human religious life. A personal relation between the vedic poet Vasiṣṭha and the merciful and compassionate god Varuṇa as presented in the rigvedic hymns is also reflected.